Developing a Peace Guidance Book to Alleviate Student Aggressiveness - Saputra, Wahyu Nanda Eka; Nurani, Wike; Fauziah, Mufied (Jurnal Kajian Bimbingan dan Konseling, 2021)
This study aims to develop a peace guidebook as a medium for school counselors in reducing student aggressiveness. The research employed research and development design proposed by Borg and Gall model, which includes identifying aggressive needs and problems, drafting a hypothetical product, and expert and user assessment of the product. The data analysis technique used descriptive analysis to describe the level of aggressiveness. In addition, this study uses Cohens Kappa’s inter-rater reliability (IRR) coefficient to identify expert and user agreement on product feasibility. The results of the descriptive analysis show that aggressiveness needs more attention from school counselors, one of which is by implementing peace guidance. The developed guidebook received an assessment from two guidance and counseling experts who have a track record in developing guidance and counseling media. User ratings were obtained from two school counselors who already have educator certificates. Based on expert and user assessments, the peace guidance manual is categorized as suitable for use by school counselors to reduce student aggressiveness. The results of this study should be used as material and consideration for further research to empirically test the peace guidance guidebook’s effectiveness in reducing student aggressiveness.